2020
DOI: 10.1038/s41598-020-72472-y
|View full text |Cite
|
Sign up to set email alerts
|

Difference in persistent tuberculosis bacteria between in vitro and sputum from patients: implications for translational predictions

Abstract: This study aimed to investigate the number of persistent bacteria in sputum from tuberculosis patients compared to in vitro and to suggest a model-based approach for accounting for the potential difference. Sputum smear positive patients (n = 25) provided sputum samples prior to onset of chemotherapy. The number of cells detected by conventional agar colony forming unit (CFU) and most probable number (MPN) with Rpf supplementation were quantified. Persistent bacteria was assumed to be the difference between MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In addition, the use of a correction factor ( ) that scaled down the ratio of the non-multiplying bacteria to the total bacteria that is transferred from the MTP model to the tube bacterial compartment was also evaluated ( . The parameter was both estimated and fixed to 17% ( Faraj et al, 2020a ). This is because it has been previously shown that the ratio of the non-multiplying sub-state to the total bacteria had to be scaled down to correctly predict the clinical bacterial number using an MTP model developed using in vitro data ( Faraj et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the use of a correction factor ( ) that scaled down the ratio of the non-multiplying bacteria to the total bacteria that is transferred from the MTP model to the tube bacterial compartment was also evaluated ( . The parameter was both estimated and fixed to 17% ( Faraj et al, 2020a ). This is because it has been previously shown that the ratio of the non-multiplying sub-state to the total bacteria had to be scaled down to correctly predict the clinical bacterial number using an MTP model developed using in vitro data ( Faraj et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…The parameter was both estimated and fixed to 17% ( Faraj et al, 2020a ). This is because it has been previously shown that the ratio of the non-multiplying sub-state to the total bacteria had to be scaled down to correctly predict the clinical bacterial number using an MTP model developed using in vitro data ( Faraj et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be employed to account for immunity, and integrate the effects of multiple drugs [72] . The exploration of phenotypic differences in persistent TB bacteria between in-vitro systems and patient sputum [73] ; computational models of granuloma formation and function [74] ; models describing the spatio-temporal distribution of drugs in granulomas and cavitary TB lesions [75] , the multi-state TB pharmacometric (MTP) model, which provides predictions of the change in bacterial counts for fast-, slow-and nonmultiplying bacterial sub-populations, with and without drug effects [ 76 , 77 ]; and models linking the MTP with the General Pharmacodynamic Interaction (GPDI) model to account for the PD interactions between concomitantly administered drugs [78][79][80] , are examples of recently developed 'sub-systems' platforms contributing to ever-more complex models informing optimal drug combinations and doses [81][82][83][84][85][86] . Models describing drug distribution to cerebrospinal fluid (CSF) have proven useful in informing the treatment of TB meningitis, with recent work linking low rifampicin [87] and isoniazid [88] concentrations in CSF to negative outcomes.…”
Section: Modelling Platforms and Quantitative Systems Pharmacologymentioning
confidence: 99%
“…See Table 1 for a summary of in vitro DD Mtb work; Figure 3 highlights the different mechanisms influencing growth heterogeneity in Mtb. While promising, much work remains to determine how the in vitro studies relate to in vivo findings; discrepancies in, for example, antibiotic response kinetics between one in vitro model of persistence and clinical sputum have been noted ( Faraj et al., 2020 ).…”
Section: Mechanisms Underlying Heterogeneity In Culturabilitymentioning
confidence: 99%